Hybrid molecules containing a 7-chloro-4-aminoquinoline nucleus and a substituted 2-Pyrazoline with antiproliferative and antifungal activity - Montoya, Alba (2016)
Fil: Fil: Montoya, Alba. Universidad del Valle. Facultad de Ciencias Naturales y Exactas. Departamento de Química. Grupo de Investigación de Compuestos Heterocíclicos (GICH); Colombia.